INTERPERSONAL COMMUNICATION STRATEGY OF THE DASAWISMA TEAM IN IMPROVING MOTHER AND CHILD PARTICIPATION IN THE POSYANDU PROGRAM IN RW.08, PALMERAH VILLAGE - Alinda Rahmatunnisa; RR Roosita Cindrakasih; Sultan Himawan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The low level of community participation, particularly among mothers and children, in Posyandu activities has become a challenge in improving the quality of community-based health services. This study aims to analyze the interpersonal communication strategies employed by the Dasawisma Team of RW.08 Palmerah in enhancing community participation in Posyandu programs. The research applied a descriptive qualitative method, utilizing in-depth interviews with Dasawisma cadres, active and less active housewives, and triangulation with a communication expert. The findings reveal that interpersonal communication was carried out with empathy, warmth, and adaptation to the social and psychological conditions of the residents. The strategies combined verbal, nonverbal, empathic, and assertive communication, both through face-to-face interactions and digital media. These approaches effectively fostered emotional closeness, strengthened trust, and encouraged active participation of residents. The novelty of this research lies in the finding that the sustainable integration of interpersonal communication, along with adjustments to residents’ characteristics, can not only enhance participation but also reinforce social solidarity within the community.